Climate Change And The Sustainable Development Goal On Food Security: Barriers And Opportunities For Progressive Realization In Qatar And Nigeria - Ajibade, Idowu; Egge, Michael; Pallathadka, Arun (Journal of Sustainable Development Law and Policy, 2025)
The United Nations Sustainable Development Goal 2 (SDG 2) contains a global commitment to “end hunger, achieve food security, and promote sustainable agriculture” by 2030. The realization of this goal under the current global political economy, climate change trends, and national realities is a daunting challenge. In this article, we draw on political ecology theory to examine the complex ecological, economic, geopolitical, climatic, and socially-induced barriers that threaten the achievement of SDG 2 in two oil producing countries with a high dependency on food imports: Qatar and Nigeria. First, we provide an overview of barriers to global food security and sustainable agriculture by discussing how the unevenness of power and resource distribution, reduced genetic diversity, land grabs, restrictive property rights, and the control of stable food production by big agri-businesses, all served to undermine hunger reduction and food security in the last 20 years. Second, drawing on newspaper analysis and an extensive literature review, we answer the questions: what are the current and future barriers to food security in Qatar and Nigeria? What efforts are these countries taking to address these barriers? What can both countries learn from one another? We also identify opportunities for new governance architecture on local food production. Finally, we suggest ways in which crucial reforms at local, national, regional and global scales might allow these countries to progressively realize SDG 2 by 2030 even under a climate change scenario.